Challenges and strategies for coping with scleroderma: implications for a scleroderma-specific self-management program. Issue 21 (9th October 2019) - Milette, Katherine; Thombs, Brett D.; Maiorino, Kristina; Nielson, Warren R.; Körner, Annett; Peláez, Sandra
Abstract: Purpose: The purpose of this study was to explore challenges faced by patients with systemic sclerosis, also called scleroderma, in coping with their disease and the strategies they used to face those challenges. Method: Five focus groups were held with scleroderma patients (4 groups, n  = 34) and health care professionals who have experience treating scleroderma (1 group, n  = 8). Participants' discussions were recorded, transcribed and analyzed using thematic analysis. Results: Participants reported challenges accessing information (e.g., knowledgeable specialists), dealing with negative emotions (e.g., stress due to misunderstandings with loved ones), and accessing resources (e.g., helpful products or devices). Strategies for overcoming challenges were also discussed (e.g., advocating for own needs). Conclusion: When faced with significant challenges while coping with scleroderma, patients develop strategies to manage better and improve their quality of life. To help them cope, patients would benefit from easier access to supportive interventions, including tailored scleroderma self-management programs. Although the challenges experienced by patients with scleroderma are unique, findings from this study might help better understand patients' perspectives regarding coping and disease management for other chronic diseases as well. Implications for Rehabilitation: People living with rare diseases, including the rare autoimmune disease scleroderma, face unique challenges and often do not have access to disease-specific educational or other support resources. People with scleroderma report that they face challenges in accessing information, including knowledgeable healthcare providers; managing difficult social interactions and negative emotions; and accessing resources. Strategies employed by scleroderma patients to overcome these challenges include seeking connections to other people with scleroderma or scleroderma patient organizations, actively seeking out local resources, and learning to communicate and advocate more effectively. Rehabilitation professionals can support people with scleroderma by providing them with information on connecting with scleroderma patient organizations or by facilitating local patient support networks.